Effect of different cyanobacterial biomasses and their fractions with variable microcystin content on embryonal development of carp (Cyprinus carpio L.) - Palíková, Miroslava; Krejcí, Roman; Hilscherová, Klára; Babica, Pavel; Navrátil, Stanislav; Kopp, Radovan; Bláha, Ludek (Aquatic toxicology (Amsterdam, Netherlands), 2007)
While numerous studies focused on the effects of microcystins, the role of other components of complex cyanobacterial water blooms in toxicity is poorly understood. In this study we have evaluated effects of various fractions of cyanobacterial biomass with different composition and microcystin content on embryolarval development of carp (Cyprinus carpio). The following samples (fractions) of four natural water blooms were prepared and tested: complex cyanobacterial biomass, crude aqueous extract of biomass, cellular pellet remaining from aqueous extract, permeate (i.e. microcystin-free fraction prepared during C-18 solid-phase extraction; SPE), and eluate (i.e. fraction prepared by SPE containing mostly microcystins). Complex biomass and the crude aqueous extract (regardless of microcystin content and/or microcystin variants present) in the sample were the most toxic. On the other hand, eluate fractions of all samples containing microcystins in concentrations 8-255 microgL(-1) induced no or only weak toxic effects. Exposures of fish to permeate fractions (with removed microcystins) of two samples dominated by Aphanizomenon sp. and Planktothrix sp. resulted in significant mortality, while other two samples dominated by Microcystis spp. induced minor effects. We have also observed significant inhibition of glutathione S-transferases (GST) at most fractions of the Aphanizomenon sp. and Planktothrix sp. dominated samples. Our data indicate that cyanobacterial water blooms as well complex biomass extracts induce significant embryolarval toxicity in common carp. However, these effects were independent of microcystin content, and the most pronounced effects were observed with the non-Microcystis dominated samples. Therefore, a critical examination of microcystin role in overall ecotoxicology of complex cyanobacterial blooms is needed.
Keywords: embryo nesavčí; Carps; kapři; mikrocystiny; Animals; Cyanobacteria; Embryo, Nonmammalian; sinice; zvířata; glutathiontransferasa; biomasa; Microcystins; Glutathione Transferase; Biomass; Aphanizomenon